Modification of Nanocrystalline Cellulose for Bioactive Loaded Films - Criado, Paula; Fraschini, Carole; Salmieri, Stéphane; Lacroix, Monique (Journal of Research Updates in Polymer Science, 2014)
Despite the use of petrochemical derived packaging, many problems such as browning and food spoilage still happen in food after harvesting. There is an increasing consumers concern for food shelf life to be extended as much as possible along with a big interest in green and bioactive materials, that could be used in direct contact with aliments. In order to reach public demand, biopolymers coming from natural sources such as plants or animals have been used to replace synthetic materials. Even though natural polymers are biodegradable, they do not reach regulations required with respect to mechanical properties in commercial applications. However, the mechanical properties can be improved when reinforced with nanoparticles. Several reinforcing nanoparticules such as clays, silica or silver have been used for industrial applications, but cellulose nanocrystals (CNCs) are a better choice for food industry due to their biodegradable and biocompatible nature as well as their outstanding potential in improving mechanical and barrier properties of nanocomposites. CNCs consist of anhydroglucopyranose units (AGU) linked together and several functional hydroxyl groups found on its surface. Modifications of the CNC surface chemistry can give to cellulose new functionalities that open the way to the development of new bioactive reinforcement in food packaging. The present review will be focused on covalent and non covalent modifications that can be achieved on surface CNC with the aim of adding functionalities to be applied for food industry.